Long-term Follow-Up of Individuals with Celiac Disease: An Evaluation of Current Practice Guidelines. (2007) - Silvester, Jocelyn A; Rashid, Mohsin
Abstract : INTRODUCTION: Celiac disease can be treated by following a strict gluten-free diet for life. If properly followed, the diet resolves symptoms and nutritional deficiencies. It is generally recommended that individuals with celiac disease have careful long-term follow-up. However, it is not clear which elements of disease status evaluation, laboratory investigations and self-management support should be included in follow-up. OBJECTIVES: To examine the current practice guidelines and recommendations regarding follow-up of individuals with celiac disease. METHODS: Guidelines issued by gastroenterological societies and associations, and recommendations by experts were retrieved using MEDLINE and other Internet search engines. RESULTS: Practice guidelines were available from the American Gastroenterological Association; the North American Society for Pediatric Gastroenterology, Hepatology and Nutrition; the National Institutes of Health Consensus Development Conference 2004; the World Gastroenterology Organization; the British Society for Gastroenterology and the United Kingdom-based Primary Care Society for Gastroenterology. Most guidelines recommended a scheduled annual review and regular measurements of body mass index. The British Society for Gastroenterology recommended dietary review only at times of stress, while others recommended dietary review with a nutritionist. All associations recommended serial tissue transglutaminase antibody testing. The American Gastroenterological Association and the Primary Care Society for Gastroenterology recommended annual hemoglobin, ferritin and folate checks. One guideline recommended annual hemoglobin, electrolyte, calcium, albumin, ferritin, folate, fat-soluble vitamin, liver function test, parathyroid hormone and bone density measurements (approximately $400 per patient). CONCLUSIONS: The current practice guidelines regarding the follow-up of patients with celiac disease varied greatly in their recommendations and many were not evidence-based. Prospective studies are required to develop rational, cost-effective and risk-stratified guidelines for long-term follow-up of these patients.